QAPLIB – A Quadratic Assignment Problem Library - Burkard, Rainer E.; Karisch, Stefan E.; Rendl, Franz (Journal of global optimization, 1997)
A collection of electronically available data instances for the QuadraticAssignment Problem is described. For each instance, we provide detailedinformation, indicating whether or not the problem is solved to optimality. Ifnot, we supply the best known bounds for the problem. Moreover we surveyavailable software and describe recent dissertations related to the QuadraticAssignment Problem.